2020
DOI: 10.3390/ijerph17207451
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Prevalence, Attitudes and Behavior among Dental Students in Poland and Italy

Abstract: The aim of the study was to perform preliminary research to compare the smoking prevalence, attitudes and behavior between dentistry students in two universities in Europe using the standardized Global Health Professions Student Survey (GHPSS) questionnaire. This was cross-sectional carried out among dentistry students from the Medical University in Bialystok, Poland and Sapienza University of Rome, Italy. There were 582 participants; 282 were Italians, 202 were smokers and 42% were Italians. The response rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 35 publications
6
14
3
Order By: Relevance
“…More than one out of five study participants reported to be current smokers. This finding confirms that in Italy smoking prevalence among dentists remains excessively high for a category of healthcare professionals who should set a good example for their patients [ 31 , 32 ]. In this population, we also observe a relatively high use of electronic cigarettes (8%) and HTPs (5%), much higher than the estimates of the general adult Italian population [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 77%
“…More than one out of five study participants reported to be current smokers. This finding confirms that in Italy smoking prevalence among dentists remains excessively high for a category of healthcare professionals who should set a good example for their patients [ 31 , 32 ]. In this population, we also observe a relatively high use of electronic cigarettes (8%) and HTPs (5%), much higher than the estimates of the general adult Italian population [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 77%
“…The nicotine concentration was calculated by the area of the peaks that appeared in the chromatogram, and by using the calibration curve equation or regression, the calculation of Standard deviation (SD), relative standard deviation (RSD%) and relative error (RE). To know the daily accuracy (inter-day), the standard solution of 20 mg/L and 30 mg/L was injected once a day for three consecutive days with a total of three iterations for each concentration, as shown in Table (2). In light of the indicator values shown in Table 3 above, the method of analysis in the near-term (Intraday) and daily range (Inter-day) was considered to be acceptable, sensitive and accurate.…”
Section: Precisionmentioning
confidence: 99%
“…Tobacco use is a major cause of death worldwide [1]. Tobacco kills more than 8 million people every year of whom more than 7 million are direct users of it and about 1.2 million are non-smokers exposed to second-hand smoke [2]. Most tobacco users live in low-and middleincome countries [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same is not observed among young Italians, among which the prevalence of smokers is over 30%, one of the highest in Europe [9]. Tobacco smoking is also relevant among undergraduates, with percentages of smokers in the 12-49% range, even among medicine and health profession undergraduates [10][11][12].…”
Section: Introductionmentioning
confidence: 99%